2021
DOI: 10.1016/j.surg.2021.04.023
|View full text |Cite
|
Sign up to set email alerts
|

Evidence Map of Pancreatic Surgery–A living systematic review with meta-analyses by the International Study Group of Pancreatic Surgery (ISGPS)

Abstract: Background: Pancreatic surgery is associated with considerable morbidity and, consequently, offers a large and complex field for research. To prioritize relevant future scientific projects, it is of utmost importance to identify existing evidence and uncover research gaps. Thus, the aim of this project was to create a systematic and living Evidence Map of Pancreatic Surgery. Methods: PubMed, the Cochrane Central Register of Controlled Trials, and Web of Science were systematically searched for all randomized c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
43
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(46 citation statements)
references
References 28 publications
2
43
0
Order By: Relevance
“…Partial pancreatoduodenectomy (PD) is the treatment of choice for numerous malignant and benign disease of the pancreas. Although postoperative mortality after PD has decreased below 5%,1 morbidity remains high even in designated pancreatic cancer centres. Postoperative complication rates of up to 40% are regularly reported in prospective studies 2–4.…”
Section: Introduction and Scientific Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…Partial pancreatoduodenectomy (PD) is the treatment of choice for numerous malignant and benign disease of the pancreas. Although postoperative mortality after PD has decreased below 5%,1 morbidity remains high even in designated pancreatic cancer centres. Postoperative complication rates of up to 40% are regularly reported in prospective studies 2–4.…”
Section: Introduction and Scientific Backgroundmentioning
confidence: 99%
“…POPF is one of the most frequent PD-associated complications occurring in 15%–30% of the patients 2 3 6 with a POPF related haemorrhage as possible result which represents the most severe complication after PD. 1 5 Multiple risk factors have been identified that are associated with the development of POPF following PD including patient-associated risk factors like body mass index (BMI), 7 perioperative risk factors and surgeon-associated risk factors (experience in PD surgery). Furthermore, a number of pancreas-associated risk factors have been proposed in the literature including histology, 8 a small diameter of the main pancreatic duct (MPD), 7 9 10 soft pancreatic texture 3 11 and a excentric location of the pancreatic duct.…”
Section: Introduction and Scientific Backgroundmentioning
confidence: 99%
See 1 more Smart Citation
“…Conversely, meta-analyses [10][11][12] showed no differences between the incidence of DGE in pylorus-preserving pancreatoduodenectomy (PPPD) and classical Whipple. This issue is controversial and a matter of concern [13].…”
Section: Introductionmentioning
confidence: 99%
“…Delayed gastric emptying, pancreatic leakage, biliary leakage, and postpancreatectomy hemorrhage (PPH) are the most common and important complications after PD. PPH occurs in 5% of patients with a 99% confidence interval of 4% to 7%, 1 and it is associated with high mortality. 2 Delayed PPH (>24 hours after PD) is always the result of multiple pathological factors, such as a pancreatic fistula and intra-abdominal abscess.…”
Section: Introductionmentioning
confidence: 99%